GdVO₄:Eu³⁺ nanoparticles - embedded CaCO₃ microspheres: synthesis and characterization - Bespalova, I.I.; Yefimova, S.L.; Tkacheva, T.N.; Hubenko, K.A.; Sorokin, A.V.; Mateychenko, P.V. (Functional Materials, 2017)
In present study, we report on synthesis of fluorescent GdVO₄:Eu³⁺ nanoparticle-embedded CaCO₃ microparticles (CaCO₃@GdVO₄:Eu³⁺) and their characterization. Synthesized CaCO₃@GdVO₄:Eu³⁺ microspheres are of vaterite polymorph and about 2 µm diameter with -12.80±0.82 mV zeta potential. The specific surface area of the CaCO₃@GdVO₄:Eu³⁺ microspheres and pore size distribution were analyzed by Brunauer-Emmett-Teller method. The microparticles was classified as macroporous ones with a wide distribution of pore sizes.The specific surface area for CaCO₃@GdVO₄:Eu³⁺ microspheres (Sbet = 25.2 m²/g) is higher than reported for CaCO₃ microparticles obtained without any additives. CaCO₃@GdVO₄:Eu³⁺ microspheres exhibit strong fluorescence both in a water solution and under fluorescent microscopy conditions that makes them attractive for bio-related application.